Ringkasan Studi Sinergi Antara Jaringan Kereta Api Perkotaan Dengan Properti Pemukiman - Kuswati, Atik S (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Kinds of urban transportation policy are used to overcome public transportation's problemin big cities. One of them is the development of public transportation based on railways.This policy has already implemented in J abodetabek as public transportation besides buses.The potency of J abodetabek railways development can be seen from the trends of passengersand land use patterns. In addition, the synergy of settlement area in cities and railwaysdevelopment can be seen as potency as well. The cooperation between PT.KA and privatecompanies has already exists and can be improved by considering the potency. The growthsof those settlements area refers to the regional planning which can take advantage fromthe railways track through on the area, conversely PT.KA will gain profit from the passengerswho stay in that area. This matter is explained in the study of The Synergy of UrbanRailways Network and Settlement Property conducted by Research and Development ofTransportation Agency in 2008.